Bagaimana Remaja Panti Asuhan Memandang Masa Depan? Pentingnya Dukungan Lingkungan - Edgart Andrean; Sari Zakiah Akmal (Psycho Idea, 2019)
Future orientation can be a protective factor for teenagers, especially orphanage adolescents who live with economic difficulties and are in members of minority groups. In adolescence the core domain of the future orientation which the major concern is related to education and occupation. The formation of future orientation can be influenced by various external or contextual factors or stated as contextual support and barrier. This research was conducted to find out the role of contextual support and barrier to the future orientation related to education and work in the orphanage adolescence in Jakarta and Bekasi. This study is an associative study with a total of 105 adolescents living in an orphanage, obtained by incidental sampling technique. This study uses adaptation of Future Expectation Scale for Adolescents (FESA) and Contextual Support and Barrier measuring instruments. The results of research showed that contextual support contributed 8,7 % to the future orientation related to education and occupation on the orphanage adolescence. Therefore, it can be said that when the orphanage adolescence feel supported by the environment (contextual factors) it can help them form a future orientation related to positive education and occupation. This result is expected to be a reference for the orphanage and the government in making programs that can help orphanage adolescent to get support and form a positive future orientation.